Difference in relationship satisfaction and adult attachment in married and cohabitating couples - Jurič, Sabina (Anthropos (Ljubljana), 2011)
Relationship satisfaction is determined by various factors such as economic and social security of partners, their constructive problem solving, mutual compacts reaching, parental supportive behavior and their adult attachment. Our study has been designed to examine the differences in relationship satisfaction and adult attachment of married and cohabiting couples. Two hundred and sixty-fi ve heterosexual couples participated in the study. Couples were asked to complete the questionnaire Experience in Close Relationship-Revised (ECRU-R) (Chris R. Fraley & Waller, 1998; Chris R. Fraley, Waller, & Brennan, 2000) and the Kansas Marital Satisfaction Scale (KMS)(Schumm, et al., 1986). As predicted results showed higher relationship satisfaction for married than cohabiting couples. There was a general trend for more securely attached partners to be more satisfied in the relationship than less securely attached. Surprisingly, the connection between adult attachment and relationship satisfaction differed in relation to participants' gender; wives were more securely attached than cohabiting women, while the difference in attachment between husbands and cohabiting men was not significant.
Keywords: marriage; zakonska zveza; zunajzakonska skupnost; partnerski odnosi; zadovoljstvo; attachment theory; navezanost; psihologija; psychology